Cover Image, Volume 25, Issue 9. (September 2017) - Stokes, Adam; Al‐Jassim, Mowafak; Norman, Andrew; Diercks, David; Gorman, Brian
Abstract : The cover image, by Adam Stokes et al., is based on the Research Article Nanoscale insight into the p‐n junction of alkali‐incorporated Cu(In, Ga)Se2 solar cells, DOI:10.1002/pip.2883 .